Social Cognition and Emotional Functioning in Patients with Binge Eating Disorder. (17th February 2017) - Aloi, Matteo; Rania, Marianna; Caroleo, Mariarita; De Fazio, Pasquale; Segura‐García, Cristina
Abstract: Objective: This study aims to evaluate the theory of mind ability in a sample of obese patients with and without binge eating disorder (BED) and to explore the correlations between emotional and clinical assessments. Methods: Overall, 20 non‐BED, 16 under‐threshold BED and 22 BED obese patients completed a battery of tests assessing social cognition and eating disorder psychopathology. Results: Binge eating disorder, non‐BED and under‐threshold‐BED obese patients showed similar ability to recognise others' emotions, but BED obese patients exhibited a deficit in recognising their own emotions as demonstrated by more impaired levels of alexithymia and interoceptive awareness and were more depressed . High positive correlations were evident between binging, depression, interoceptive awareness and alexithymia. Conclusions: Binge eating disorder patients have a comparable ability to understand others' emotions but a more impaired capacity to understand and code their own emotions compared with non‐BED obese patients. This impairment is highly correlated with depression. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.